Acquiring practice in environmental and social impact assessment: case study of Lviv city dumpsite, Ukraine - Mykhaylenko, Valeriy; Havryliuk, Ruslan; Blyzniuk, Mykola; Kriipsalu, Mait; Hoffmann, Michael; Denafas, Gintaras; Sholokhova, Anastasiia; Hogland, William; Nauchu, Nataliia; Gulevets, Dmytro (Видавництво Львівської політехніки, 2021)
Municipal Solid Waste Management (MSWM) is a new and fast-growing business area that is becoming widespread in Ukraine. The fire accident at Lviv city landfill “Hrybovychi” forced the local governments to initiate work on its closure and reclamation. The Environmental Impact Assessment (EIA) of the planned activity is the first mandatory step in this direction. The complex nature of EIA procedures requires a similarly integrated approach to identify hazards and develop a shared vision of existing risks. This is demonstrated by the analysis of two published EIA reports on remediation of “Hrybovychi” dump and the dangers that were not identified. Threats of additional groundwater pollution, causes of fire and consequences of negative impact on adjacent areas, the possibility of re-ignition of the landfill, the spreading of microparticles (PM2,5), and formation of toxic compounds classified as persistent organic pollutants (POPs) together with their long-distance migration – these and other dangers were not identified and were not discussed with public organizations. The article aims at showing a scientific approach to identifying environmental hazards in combination with the social component – assessments of problematic activities for public health, which are often ignored in post-Soviet countries. Current and best practices of the Baltic Sea countries in this field are presented by an international team of university scientists. Analysis of critical observations and making recommendations for preventing, minimizing, and mitigating the adverse effects of an accident can help to improve the peer review and development of similar EIA projects.
Keywords: Municipal Solid Waste (MSW); landfill gases; pollutant emissions; environmental impact assessment (EIA); persistent organic pollutants (POPs); leachate; heavy metals